Distribution of concurrent training sessions does not impact endurance adaptation. Issue 3 (March 2021) - Kilen, Anders; Bay, Jonathan; Bejder, Jacob; Breenfeldt Andersen, Andreas; Bonne, Thomas; Larsen, Pernille; Carlsen, Andreas; Egelund, Jon; Nybo, Lars; Vidiendal Olsen, Niels; Aachmann-Andersen, Niels Jacob; Løvind Andersen, Jesper; et al.
Abstract: Objectives: Optimized concurrent training regimes are warranted in physical training of military-, law enforcement- and rescue-personnel. This study investigated if four 15-min endurance training sessions weekly improve aerobic capacity and performance more than one 60-min endurance session weekly during the initial phase of a Basic Military Training program. Design: A randomized training intervention study with functional and physiological tests before and after the intervention. Methods: Military conscripts (n = 290) were randomly allocated to three groups completing 9 weeks training. Weekly training consisted of four endurance and four strength training sessions lasting 15 min each ('Micro-training': MIC); one strength and one endurance session lasting 60 min each ('Classical-training': CLA) or two 60 min sessions of standard military training ('Control-training': CON). Results: Both 12-min (∼7−10%) and shuttle run performance (∼35−42%) improved (P ≤ 0.001) similarly in all groups. Likewise, functional 2-min maximal repetition exercise capacity increased (P ≤ 0.05) similarly in all groups (Lunges ∼17−24 %; PushUp ∼10−20%; AbdominalFlexions∼21−23%). Peak oxygen uptake changes depended on group (P ≤ 0.05) with increases (P ≤ 0.01) in MIC (7 ± 7%, n = 23) and CON (12 ± 18%, n = 17) and no changes in CLA. Maximal m. vastus lateralis citrate synthase activity decreased 14 ± 26% (P ≤ 0.001, n = 18) in CLA. Likewise, maximal m. vastus lateralis 3-hydroxyacyl-CoA dehydrogenase activity decreased 8 ± 17% in MIC (n = 28) and 14 ± 24% in CLA (n = 18). Conclusions: Four 15-min endurance training sessions weekly improves running performance and strength-endurance similarly to one 60 min session. Peak oxygen uptake only increases with more than one endurance session weekly and leg muscle oxidative capacity appears reduced after basic military training.